EVALUATING THE IMPACT OF BRAND IMAGE, PRICE AND HALAL CERTIFICATION ON UNIVERSITY STUDENTS PURCHASE DECISIONS OF ORIFLAME MAKEUP - Manullang, Elia Berliana; Puruwita, Dita; Fawaiq, Muhammad (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2024)
The purpose of this study was to determine the effect of brand image, product price and halal label on purchasing decisions of Oriflame makeup products. This study uses quantitative research methods. Primary data were collected through a questionnaire with a Likert scale that reflects five points from strongly agree to strongly disagree. The sample selection technique used was purposive sampling. The sample criteria in this study were students of the State University of Jakarta who had purchased Oriflame products in the last six months, the sample in this study was 150 respondents and were between 18 and 34 years old. The data analysis technique in this study used SPSS 24 software. The results of this study indicate that brand image has a positive and significant effect on purchasing decisions, product prices have a positive and significant effect on purchasing decisions and product halal labels have a positive and significant effect on purchasing decisions.